1967
DOI: 10.1111/j.1151-2916.1967.tb15043.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Crystallization of Li2O-Al2O3-SiO2 Glasses Containing TiO2

Abstract: The nucleation and crystallization of Li2O‐Al2O3‐SiO2 glasses containing TiO2 were investigated using transmission electron microscopy of thin sections produced from bulk samples. Phase separation occurs during cooling from the melt, and on heating, a large number of titanium‐aluminum crystals approximately 50 A in diameter are formed. These crystals are the heterogeneous nuclei for the crystallization of the remaining glass. Photomicrographs of various stages of crystallization show the development of the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(22 citation statements)
references
References 4 publications
3
18
1
Order By: Relevance
“…When a proper amount of TiO2 was added to the Li2O-Al2O3-SiO2 glass, phase separation was developed at the nucleation stage, which led to the formation of β-quartz ss (Figures 3 and 4). This is consistent with previous reports that the addition of TiO2 produced a TiO2-rich phase and serves as a nucleation phase for the formation of β-quartz ss (Doherty et al, 1967;Barbieri et al, 1997b,c;Nordmann and Cheng, 1997;Bhattacharyya et al, 2009). In contract, the TiO2-free glass remained amorphous at this nucleation stage (Figure 3).…”
Section: Discussionsupporting
confidence: 92%
“…When a proper amount of TiO2 was added to the Li2O-Al2O3-SiO2 glass, phase separation was developed at the nucleation stage, which led to the formation of β-quartz ss (Figures 3 and 4). This is consistent with previous reports that the addition of TiO2 produced a TiO2-rich phase and serves as a nucleation phase for the formation of β-quartz ss (Doherty et al, 1967;Barbieri et al, 1997b,c;Nordmann and Cheng, 1997;Bhattacharyya et al, 2009). In contract, the TiO2-free glass remained amorphous at this nucleation stage (Figure 3).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, several investigators [23,24] showed that in glasses containing appreciable amounts of TiO 2 the effective nuclei and small crystallites of titanium are compound such as titanates.…”
Section: Role Of Titanium Dioxide (Tio 2 )mentioning
confidence: 99%
“…Crystallisation of Li 2 O-CaO-SiO 2 glass-ceramics in traditional processes is generally achieved using small additions of oxides, particularly TiO 2 [20][21][22], ZrO 2 [23,24], or a combination of both [25,26] to the base glass. In the present work, it was found that the Li 2 O-CaO-SiO 2 system glass with ZrO 2 and TiO 2 had high crystallisation tendency upon heat-treatment.…”
Section: Crystallisation Characteristicsmentioning
confidence: 99%